2021
DOI: 10.3389/fneur.2021.687624
|View full text |Cite
|
Sign up to set email alerts
|

Passive Properties of the Wrist and Fingers Following Chronic Hemiparetic Stroke: Interlimb Comparisons in Persons With and Without a Clinical Treatment History That Includes Botulinum Neurotoxin

Abstract: Background: Neural impairments that follow hemiparetic stroke may negatively affect passive muscle properties, further limiting recovery. However, factors such as hypertonia, spasticity, and botulinum neurotoxin (BoNT), a common clinical intervention, confound our understanding of muscle properties in chronic stroke.Objective: To determine if muscle passive biomechanical properties are different following prolonged, stroke-induced, altered muscle activation and disuse.Methods: Torques about the metacarpophalan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 69 publications
0
8
0
Order By: Relevance
“…In a recent study that compared passive properties of spastic wrist and finger flexors in chronic stroke survivors, no significant differences in passive torques between affected and contralateral limbs were found in those who never received BoNT. In contrast, passive torques were significantly higher and passive range of motion of wrist and finger extension was significantly smaller in the affected limb than the contralateral limb in those who received BoNT injections to these muscles, on average, 4 and 1/2 years ago [43]. In another study [44], stroke subjects received either BoNT or placebo (normal saline) injections when spasticity was first detected in the arm flexors.…”
Section: Bont Effects On Elbow Flexor Spastic Hypertoniamentioning
confidence: 99%
“…In a recent study that compared passive properties of spastic wrist and finger flexors in chronic stroke survivors, no significant differences in passive torques between affected and contralateral limbs were found in those who never received BoNT. In contrast, passive torques were significantly higher and passive range of motion of wrist and finger extension was significantly smaller in the affected limb than the contralateral limb in those who received BoNT injections to these muscles, on average, 4 and 1/2 years ago [43]. In another study [44], stroke subjects received either BoNT or placebo (normal saline) injections when spasticity was first detected in the arm flexors.…”
Section: Bont Effects On Elbow Flexor Spastic Hypertoniamentioning
confidence: 99%
“…44 More recently, research has shown that repeated use of BoNT may also lead to decreased passive muscle capacity. 13 Studies done in rodents indicated that BoNT injection led to a decrease in function, range of motion, and an increase in passive resistance. [45][46][47][48] A systematic review examining BoNT injections in humans and animals found similar results, such as lingering muscle atrophy and changes in muscle elasticity.…”
Section: Effect Of Botulinum Toxin By Adverse Effectsmentioning
confidence: 99%
“…However, recent evidence suggests that the nature of the toxin may lead to muscle shortening and a restricted range of motion if repeatedly injected. 13 This paper will provide a scoping review on the effectiveness of Botulinum Toxin for post-stroke arm dysfunction and its overall effect on the patient.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of hyperactive stretch reflexes, in comparison, may not play a major role in stroke disability ( 5 ) compared to the expression of said flexion synergy ( 11 ). As passive muscle properties are also largely unchanged ( 4 , 12 ), it is likely the overactive wrist and finger flexors ( particularly the flexion synergy) and extensor weakness that limits hand use in stroke.…”
Section: Introductionmentioning
confidence: 99%
“…Some individuals even develop neutralizing antibodies to the toxin, rendering the intervention ineffective with repeat injections ( 28 ). Finally, evidence also indicates potential long-term concerns related to increased muscle passive stiffness, possibly due to muscle extracellular matrix proliferation ( 12 , 29–32 ). An alternative worth exploring is the use of FES-based methods that provide instantaneous, controllable, and reversible blocking of peripheral nerve transmission ( 33–35 ).…”
Section: Introductionmentioning
confidence: 99%